WATER EXPLOITATION AND ITS OUTCOMES CAUSED BY CAPITALISM AS REFLECTED ON GORE VERBINSKI’S RANGO MOVIE - SETIAWAN, DANIEL NUGRAHA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Nugraha Setiawan, Daniel. 2014. Water Exploitation and Its Outcome Caused byCapitalism as Reflected on Gore Verbinski’s Rango Movie. Study Program ofEnglish, Universitas Brawijaya.Supervisor: Yusri Fajar, Co-supervisor: Melania Shinta Harendika.Keywords: water exploitation, environment, capitalism, Rango movie. Water exploitation threats ecosystem and causes a great damage to environment. One of the causes of the water exploitation is capitalism. The movie entitled Rango reveals some causes and effects of water exploitation caused by capitalism inside the movie.This research applies eccocriticism approach as the main study to analyze thismovie entitled Rango. This study also applies the concept of capitalism and movie studies. The result of the study reveals that water exploitation causes many effects to the environment. In the movie, Mayor who becomes the main antagonist exploits all water sources for his own benefit. The water exploitation causes many bad effects for such three aspects as plant, animal, and the citizen of Dirt City. Those effects cause imbalance to the cycle of ecosystem which disrupt the life of many living beings.For future researchers, it is advisable to conduct further studies on the samemovie but with different approaches. One of the examples is Marxism approach,because Marxism approach can be used to analyze the struggle of the citizen of Dirt City to get enough water.